REAKTUALISASI NILAI-NILAI PANCASILA DALAM SISTEM PENDIDIKAN NASIONAL - Saiin, Asrizal (Justitia et Pax, 2017)
The background of this article is to look at the current phenomenon of public understanding, particularly regarding today’s students’ generation who has begun to forget Pancasila values. Moral degradation of current the generation becomes a big problem in this nation, comparable to corruption, robbery, murder, until the problem of repression and violence for the sake of religion. Because of such reason, there is a need to renew and reinvestthe values of Pancasila in school institutions. This research normative legal research, namely research that employs secondary data obtained through the literature study. As stipulated in the Law No. 20 of 2003 about National Education System, particularly in regard to the elaboration of Article 37 paragraph (1) that education is meant to form the students to become a religious human being, kind-hearted and having a good ethic. The author tries to give a new color to the national education system about the valuesof Pancasila that should be actualized in the development of national education. The solution is to re-actualize the values of Pancasila. Indonesia national education should be re-motivated on the basis of Pancasila ideology, both as a state’s ideology and as the personality of the nation.Keywords: Reactualisation, Pancasila Values, National Education System.IntisariLatar belakang artikel ini adalah melihat fenomena sekarang bahwa pemahaman masyarakat umum khususnya generasi pelajar saat ini sudah mulai lupa dengan nilainilai Pancasila. Degradasi moral generasi zaman sekarang menjadi persoalan besar bangsa ini, seperti korupsi, perampokan, pembunuhan, bahkan sampai pada masalah kekerasan dan penindasan atas nama agama. Berawal dari hal demikian, perlu adanya pembaharuan penanaman kembali nilai-nilai Pancasila di instansi sekolah. Penelitianini merupakan penelitian hukum normative, yaitu penelitian terhadap data sekunder yang diperoleh melalui studi pustaka. Sebagaimana tertuang di dalam Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional, terutama penjelasan Pasal 37 ayat (1) bahwa pendidikan dimaksudkan untuk membentuk peserta didik menjadi manusia beriman, bertakwa dan berbudi pekerti yang baik. Dari sini penulis berusaha untuk memberikan warna baru dalam sistem pendidikan nasional tentang nilainilai Pancasila yang seharusnya diaktualisasikan dalam pengembangan pendidikan nasional. Solusinya adalah mengaktualisasikan kembali nilai-nilai Pancasila. Pendidikan nasional Indonesia hendaknya harus diberi motivasi kembali atas dasar ideologis Pancasila, baik secara ideologi negara maupun kepribadian bangsa.Kata kunci: Reaktualisasi, Nilai-nilai Pancasila, Sistem Pendidikan Nasional.